2003
DOI: 10.1104/pp.103.024422
|View full text |Cite
|
Sign up to set email alerts
|

Peptide and Amino Acid Transporters Are Differentially Regulated during Seed Development and Germination in Faba Bean

Abstract: Two peptide transporter (PTR) homologs have been isolated from developing seeds of faba bean (Vicia faba). VfPTR1 was shown to be a functional peptide transporter through complementation of a yeast mutant. Expression patterns of VfPTR1 and VfPTR2 as well as of the amino acid permease VfAAP1 (Miranda et al., 2001) were compared throughout seed development and germination. In developing seeds, the highest levels of VfPTR1 transcripts were reached during midcotyledon development, whereas VfAAP1 transcripts were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 64 publications
1
53
1
Order By: Relevance
“…In the past few years, using degenerate primers designed to conserved regions of peptide transporters, homologous genes encoding peptide transporters have been identified in barley [18], Vicia faba [45], and the carnivorous plant, Nepenthes, [46]. The barley scutellar peptide transporter, HvPTR1, is the best characterized plant PTR, as peptide transport in germinating barley grain has been extensively studied using biochemical approaches [18,47,48].…”
Section: The Ptrs In Barleymentioning
confidence: 99%
“…In the past few years, using degenerate primers designed to conserved regions of peptide transporters, homologous genes encoding peptide transporters have been identified in barley [18], Vicia faba [45], and the carnivorous plant, Nepenthes, [46]. The barley scutellar peptide transporter, HvPTR1, is the best characterized plant PTR, as peptide transport in germinating barley grain has been extensively studied using biochemical approaches [18,47,48].…”
Section: The Ptrs In Barleymentioning
confidence: 99%
“…Expression of AtPTR5 in the peptide transport-deficient and His auxotroph yeast (Saccharomyces cerevisiae) strain LR2 showed that, similar to other members of subfamily II, AtPTR5 mediates growth when using selective concentrations of His-Ala (1 mM) as sole source of His ( Fig. 2; Frommer et al, 1994;Rentsch et al, 1995;West et al, 1998;Miranda et al, 2003;Dietrich et al, 2004). Interestingly, the Arabidopsis di-and tripeptide transporters AtPTR1 and AtPTR2 also mediated growth on selective concentrations of His (6 mM), although affinity for His and transport rates seem to be rather low (Frommer et al, 1994;Chiang et al, 2004;Dietrich et al, 2004).…”
Section: Atptr5 Transports Dipeptides When Expressed In Yeast and Xenmentioning
confidence: 99%
“…Several members of subfamily II (see below) and one member of subgroup III (AtPTR3, At5g46050) are confirmed transporters for di-and tripeptides (Karim et al, 2005(Karim et al, , 2007Rentsch et al, 2007). Species with confirmed peptide transporters in subgroup II include Arabidopsis (AtPTR1, AtPTR2), fava bean (VfPTR1), Hakea actities (HaPTR4), and barley (HvPTR1; Frommer et al, 1994;Rentsch et al, 1995;West et al, 1998;Miranda et al, 2003;Dietrich et al, 2004). Subfamily II also contains several noncharacterized genes from Arabidopsis and other species (Fig.…”
mentioning
confidence: 99%
“…The diurnal and spatial expression profiles of AAP genes are diverse, and further studies are required to unravel their potential roles in the control of amino acid levels in the developing seeds, as recently described for orthologous AAPs in Arabidopsis and pea (Pisum sativum; Weigelt et al, 2008;Sanders et al, 2009). In addition to amino acids, phloem-derived peptides contribute significantly to the nitrogen status and regulate development in developing seeds (Miranda et al, 2003;Li et al, 2009). The diurnal expression of 11 peptide transporter genes points at a tight diurnal control of the nitrogen status in seeds via peptide import (Supplemental Table S3).…”
Section: Nitrogen Signaling May Regulate Gene Expression In Developinmentioning
confidence: 99%